VD_FINDINFO Jug / 2022 / 48 vom 24. Juni 2021 - VD Tribunal cantonal (2021)
MENACEDROIT PÉNAL, INJURE, PRINCIPE DE L'ACCUSATION, LIBRE APPRÉCIATION DES PREUVES, CONSTATATION DES FAITS, PRÉSOMPTION D'INNOCENCE | 177 CP, 180 CP, 10 CPP (CH), 324 CPP (CH), 344 CPP (CH), 9 CPP (CH)